EFFECTIVE DISSEMINATION OF AGING PROGRAMS: THE CORNELL INSTITUTE FOR TRANSLATIONAL RESEARCH ON AGING (CITRA). (11th November 2018) - Cope, M; Pillemer, K; Schultz, L
Abstract: There has been an enormous proliferation of evidence-based programs in the field of gerontology. However, sustaining dissemination after program funding has expired is challenging. We report on the development and evaluation of a web-based dissemination model for aging programs, aimed to continue their availability on a long-term basis. Over the past two decades, CITRA has created and evaluated programs in four areas of importance for older adults: active aging, long-term care, intergenerational relations, and translational tools. Programs include but are not limited to: Retirees in Service to the Environment, which engages older adults in environmental volunteering; Partners in Caregiving, which promotes family-staff cooperation in long-term care; Resident-to-Resident Elder Mistreatment, which trains long-term care staff to recognize and address it in their own facilities; and Building a Community Legacy Together, which creates meaningful intergenerational interactions to combat ageism and help older adults pass on their knowledge to younger generations. Additionally, CITRA has created methods for conducting translational research in aging, such as an innovative research-to-practice consensus workshop model. To promote uptake and sustainability, a model website was created that offers the programs in a user-friendly, downloadable format; provides easy access to journal articles on the programs and supplementary materials; and offers on-line assistance in conducting the programs. A tracking system provides information on users of the website. We present data on uptake of programs, as well as the results of a survey of users of the site regarding their experiences. Implications for dissemination of aging-related programs is discussed.